2019
DOI: 10.1142/s0219519419400165
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Simulation of the Relationship Between Foot Position and Stress of the L4–l5 Joint in Supporting Standing-Up Motion to Prevent Low Back Pain Among Caregivers

Abstract: Most caregivers have low back pain which results from frequent care activities such as assistance motion that supports transfer and standing-up. Various parameters are associated with the caregiver’s lumbar load. In this study, we focus on the foot position of the caregiver as one of the subjective adjustable parameters. This study aimed to analyze the relationship between foot position and stresses of the L4–L5 joint as lumbar load during supporting standing-up via musculoskeletal simulation. The musculoskele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…It was observed that minimum rather than maximum flexion of the lumbar spine occurred at initial contact and that flexion increased early in the single-support phase of the gait cycle. Kitagawa et al 14 studied the link between foot position and load of the L4-L5 spinal segments as lower back load during supporting standing-up via musculoskeletal simulation in the group of caregivers. It was shown that as the anteroposterior distance and lateral widths between both feet increased, the average value of compression of the L4-L5 segments during movements decreased.…”
mentioning
confidence: 99%
“…It was observed that minimum rather than maximum flexion of the lumbar spine occurred at initial contact and that flexion increased early in the single-support phase of the gait cycle. Kitagawa et al 14 studied the link between foot position and load of the L4-L5 spinal segments as lower back load during supporting standing-up via musculoskeletal simulation in the group of caregivers. It was shown that as the anteroposterior distance and lateral widths between both feet increased, the average value of compression of the L4-L5 segments during movements decreased.…”
mentioning
confidence: 99%
“…These results suggested that foot-position #9 with the longest feet-distance may cause greater load on erector spinae muscles than other foot-position. According to our previous study 7 ) , foot-position #9 with the longest feet-distance could reduce stress of lumber vertebral, but these results suggested that this placement was not optimum for low load motion to prevent lower back pain because it caused load on the erector spinae muscles. Because there were many significantly different iEMG values in only the right spinae muscles, it is hypothesized the that foot-position affected the load of the right erector muscles in the rear lower limb that was involved.…”
Section: Discussionmentioning
confidence: 90%
“…These results show that foot-position #7 (anterior-posterior 55%, lateral-medial 20% of body height) could use lower limb muscles instead of the lower back without increasing loads on erector spinae muscle. In addition, foot-position #7 uses longer feet-distance which is effective in reducing lumbar vertebral stress 7 ) . Furthermore, longer anteroposterior feet-distance is effective for moving COG of patient in supporting standing-up 23 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that surface EMG is useful for evaluating lumbar load11 ) . However, low back pain is associated with stress of the lumbar vertebra10, 12 ) and muscle cross-sectional areas13, 14 ) . We evaluated the patient handling motions to the doll to fix several factors.…”
Section: Discussionmentioning
confidence: 99%